2012
DOI: 10.1016/j.foodchem.2012.02.169
|View full text |Cite
|
Sign up to set email alerts
|

New insights into antioxidant activity of Brassica crops

Abstract: antioxidant activity of Brassica crops were related to differences in total phenolic 15 content but also to differences in phenolic composition for most samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 30 publications
8
64
0
Order By: Relevance
“…There was significant higher (61%) TEAC in spring than autumn in non-irrigated plants, in 2011. In both years the highest values were measured in the spring treatments (Table 2), which is explicable by near abiotic stress proof environment [44]. Antioxidant activities are highly correlated with phenolic compounds [40] and glucosinolates [45] and the climatic factors are very important because they can interfere in the chemical biosynthesis and therefore affect the final concentration of bioactive compounds [11,40,46].…”
Section: Teacmentioning
confidence: 95%
“…There was significant higher (61%) TEAC in spring than autumn in non-irrigated plants, in 2011. In both years the highest values were measured in the spring treatments (Table 2), which is explicable by near abiotic stress proof environment [44]. Antioxidant activities are highly correlated with phenolic compounds [40] and glucosinolates [45] and the climatic factors are very important because they can interfere in the chemical biosynthesis and therefore affect the final concentration of bioactive compounds [11,40,46].…”
Section: Teacmentioning
confidence: 95%
“…Moreover, germination increases the content in antioxidant compounds (like polyphenols, vitamins) and thereby the antioxidant potential of the plant material (Frias et al, 2005). Phenolic compounds are produced in plants through the phenylpropanoid pathway and contribute substantially to the antioxidant capacity of Brassica oleracea varieties, as they are known to be their major antioxidants (Podsedek, 2007;Soengas et al, 2012;Kaulmann et al, 2014). López-Amorós et al (2006) found that germination modifies quantitatively and qualitatively the phenolic composition of peas, lentils and beans, and the changes depend on the type of plant and germination conditions.…”
Section: Extractionmentioning
confidence: 99%
“…Brassicaceae are known to contain flavonoids (Soengas et al 2012), and especially flavonols (Pollastri, Tattini 2011;Agati et al 2012). Quercetin and kaempferol are the main representatives of the flavonols (Manach et al 2004).…”
mentioning
confidence: 99%